Plasma α‐synuclein and phosphorylated tau 181 as a diagnostic biomarker panel for de novo Parkinson's disease. Issue 6 (18th March 2022) - Ren, Jingru; Pan, Chenxi; Wang, Yajie; Xue, Chen; Lin, Huixia; Xu, Jianxia; Wang, Hui; Zhang, Wenbin; Xu, Pingyi; Chen, Yong; Liu, Weiguo
Abstract: The use of a diagnostic panel comprising multiple biomarkers has the potential to accurately diagnose Parkinson's disease (PD). However, a panel consisting solely of plasma biomarkers to diagnose PD is not available. This study aimed to examine the diagnostic ability of plasma biomarker panels for de novo PD using novel digital ultrasensitive immunoassay technology. We recruited 45 patients with de novo PD and 20 healthy controls (HCs). The concentrations of plasma α‐synuclein (α‐syn), amyloid β‐42 (Aβ42), Aβ40, phosphorylated tau 181 (p‐tau181), neurofilament light (NFL), and glial fibrillary acidic protein (GFAP) were quantified using the ultrasensitive single molecule array (Simoa) platform. Patients with de novo PD had higher plasma levels of α‐syn and p‐tau181 than HCs, adjusting for age and sex. Plasma levels of α‐syn and p‐tau181 were positively correlated in de novo PD patients. Higher plasma α‐syn levels were significantly associated with worse Unified Parkinson's Disease Rating Scale (UPDRS) Part III motor scores, modified Hoehn and Yahr (H‐Y) stages, and increased risk of PD with mild cognitive impairment (PD‐MCI). Higher plasma p‐tau181 concentrations were linked to worse H‐Y stages. The diagnostic panel using plasma α‐syn and p‐tau181, combined with age and sex, showed good performance in discriminating de novo PD patients from HCs (area under the curve = 0.806). These findings suggest that plasma α‐syn and p‐tau181 together may be a promising diagnostic biomarker panel for de novo PD patients. Abstract : To examine the diagnostic ability of plasma biomarker panels for de novo Parkinson's disease (PD), we used the ultrasensitive single molecule array (Simoa) HD‐X Analyzer to quantify the concentrations of plasma α‐synuclein (α‐syn), amyloid β‐42 (Aβ42), Aβ40, phosphorylated tau 181 (p‐tau181), neurofilament light (NFL), and glial fibrillary acidic protein (GFAP). Data showed that the diagnostic panel using plasma α‐syn and p‐tau181, combined with age and sex, showed good performance in discriminating de novo PD patients from HC (area under the curve 0.806). Plasma α‐syn and p‐tau181 may be a promising diagnostic biomarker panel for de novo PD patients.